Features of the formation of a system of ESG–indicators of non–financial reporting to assess the business activity and trustworthiness of counterparties - N. A. Lazareva (Путеводитель предпринимателя)
At present, the tasks of the «green» economy, social planning and corporate governance are of particular importance. In Russia, the concept of ESG (environment, social, governance) is at the initial stage of its development, gradually being introduced into the financial and economic activities of an economic entity. Most foreign companies, in an effort to increase or maintain a high level of business reputation, already include ESG indicators in their reports.In this regard, the purpose of this article is to study the problems associated with the formation of effective partnerships, the planning and implementation of which should be based on the use of a whole range of criteria: a positive credit history, a company’s rating in the industry, business reputation, as well as non–financial indicators that make up ESG — the concept of company development.The purpose of the study was to identify key factors on the basis of which the reliability of counterparties should be determined, a single concept should be formed in establishing criteria for assessing the integrity of counterparties, and preventing possible business risks. The importance and relevance of the study are determined by the fact that it was carried out as part of the implementation of new regulations to introduce the concept of a «technical company», assess the reliability of counterparties, and lay responsibility on companies for interacting with unscrupulous subjects of market relations.